2017
DOI: 10.1213/ane.0000000000001657
|View full text |Cite
|
Sign up to set email alerts
|

Remote Effects of Electromagnetic Millimeter Waves on Experimentally Induced Cold Pain: A Double-Blinded Crossover Investigation in Healthy Volunteers

Abstract: We were able to partially confirm the previously suggested hypoalgesic effects of low-intensity electromagnetic MW. However, the effect was indistinguishable from the placebo condition in our investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For analysis, 94 publications were identified and selected from the accessible databases (in vivo and in vitro) [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis, 94 publications were identified and selected from the accessible databases (in vivo and in vitro) [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
“…In the 40.1–50 GHz frequency group, 26 studies were identified, 13 in vivo [16,17,26,48,49,51,53,65,69,74,80,84,98] and 13 in vitro [29,30,31,62,64,86,89,92,93,100,105,107] with nine studies showing responses. A large number of studies have tested cell biology endpoints such as cell proliferation, gene or protein expression, and changes in oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few decades, considerable evidence has shown that non-thermal exposure to low intensity extremely high frequency electromagnetic fields (EHF-EMF), in the range of 40 GHz-130 GHz 1 , can induce biological changes both in vivo and in vitro , including gene expression 2 , cell proliferation 3 , and nerve cell function 4 . It can also be conducive to the treatment of neurological disorders 5 , 6 . Specifically, changes in neuronal firing rate and plasma membrane properties were reported in mouse cortical slices 7 .…”
Section: Introductionmentioning
confidence: 99%